Expressiv : Mitteleuropäische Kunst seit 1960. - Beke, László; Hermansdorfer, Mariusz; Mladek, Meda; Ronte, Dieter; Susovski, Marijan; Museum des 20. Jahrhunderts, Wien; Hirshhorn Museum and Sculpture Garden, Washington (Wien : Museum Moderner Kunst, 1987)
Abakanowicz, Magdalena ; Baranyay, András ; Beres, Jerzy ; Birkás, Akos ; Dwurnik, Edward ; Erdély, Miklós ; Frohner, Adolf ; Gustowska, Izabella ; Hasior, Wladyslaw ; Jetelová, Magdalena ; Jovánovics, György ; Kozaric, Ivan ; Kulmer, Ferdinand ; Lassnig, Maria ; Lukomski, Józef ; Malich, Karel ; Naceradsky, Jiri ; Nepras, Karel ; Neskovic, Predrag ; Nitsch, Hermann ; Novák, Ladislav ; Oberhuber, Oswald ; Popovic, Mica ; Rainer, Arnulf ; Ruzic, Branko ; Schwarzkogler, Rudolf ; Seder, Djuro ; Simotová, Adriena ; Slavik, Otakar ; Vesely, Ales
Expressiv : Mitteleuropäische Kunst seit 1960 / Central European Art since 1960, Museum Moderner Kunst / Museum des 20. Jahrhunderts, Wien, 30.11.1987 - 26.01.1988 ; Hirshhorn Museum und Sculpture Garden, Washington, 18.02.1988 - 17.04.1988
Duits & Engels
kunstcatalogus
Keywords: Centraal-Europa; Hongarije; Polen; Tsjechoslowakije; Oostenrijk; Joegoslavië